When Our Ship Comes In: The Cultural Impact of Cruise Tourism on Northern Canadian Communities - Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 2021)
This chapter explores risks to environmental, economic, social, and cultural sustainability in Northern Canaidian communities, as well as the complicated relationship between creative practices, cultural tourism, Indigenous/ Inuit values and world views, and local planning practices in this part of Canada. It also discusses some of the ethical and practical implications of Inuit–cruise passenger interactions, and explores the adaptive capacities of these communities to cope with larger and more frequent cruise tourism incursions.
Keywords: Creative Tourism; Northern Canada